Translation techniques of Islamic finance and economic terms in Arabic-English dictionaries / Antar Fuad Ali Al-Harazi - Antar Fuad , Ali Al-Harazi (2023)
The general aim of the current research is to study translation techniques employed in rendering Islamic financial and economic terms (IFETs) in bilingual Arabic-English dictionaries within the context of semantic fields. The three specific aims of the study are: (i) to investigate the semantic fields that may be utilized to classify IFETs (ii) to identify the translation techniques most frequently employed in each semantic field by the dictionary compilers of the five Arabic-English dictionaries selected for this study to provide English equivalents to the IFETs in Arabic, and (iii) to recommend translation techniques which could render adequate meanings for the IFETS undocumented in the five selected Arabic-English dictionaries in this study. The data comprises a hundred samples of IFETS randomly selected from a monolingual dictionary called ‘Dictionary of Financial and Economic Terms in the Register of Jurists’ (DFETRJ) by Hammad (2008) Based on a classification of semantic fields by Ash-Shay'a (2004), the researcher could only employ fifteen semantic fields to classify most of the selected IFETs. To classify some of the samples which did not fit into any of the fifteen semantic fields, five additional semantic fields were devised in collaboration with an IIUM academic staff who is an expert in Islamic economics. The research was thus able to present a total of twenty semantic fields to classify IFETs which the researcher believes would be very beneficial for indexing semantically related entries in lexicographic work. Next, to examine the range of translation techniques used to provide English equivalents to the IFETs, the researcher adopted the translation technique typology proposed by Mona Baker (2018) alongside typologies proposed by other scholars. Overall, nine translation techniques were found to be used by dictionary compilers. They are superordinate, subordinate, synonym, paraphrase, definition, mixed translation, loan translation, loan word and antonym. The study revealed that mixed translation and synonym were the most frequently used techniques by the dictionary compilers. Since IFETs are culturebound terms, the mixed translation technique is clearly the most suitable to render IFETs into English without loss of meaning. The findings also showed that antonyms were seldom used while definition and loan words were less frequently employed. The results also showed that out of the hundred IFETs randomly selected, only eighty-six IFETs could be found in the selected five Arabic-English dictionaries. Twenty-four IFETs were not lexicalized. This brought to light the need for more extensive work in lexicographic work related to IFETs. Accordingly, the researcher requested two professional translators to provide English equivalents for the twenty-four undocumented IFETs. The researcher’s techniques used in rendering the equivalents for the twenty-four undocumented IFETs were compared with the those employed by the other two translators to identify the most frequently used techniques and the adequacy of the English equivalents provided. The researcher recommends improvement of current dictionaries, paper or online, specialized or general ones with regard to incorporating more specialized terms in their item list and providing comprehensive meanings via the use of techniques like the mixed translation. As this study was limited to a sample of only a hundred IFETs, further research with a bigger sampling would be beneficial for more insight into other semantic fields that IFETs can be classified into and the translation techniques that can be suitably employed in lexicographic work.